2019
DOI: 10.1101/687194
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systematic phenomics analysis of ASD-associated genes reveals shared functions and parallel networks underlying reversible impairments in habituation learning

Abstract: A major challenge facing the genetics of Autism Spectrum Disorders (ASD) is the large and growing number of candidate risk genes and gene variants of unknown functional significance.Here, we used Caenorhabditis elegans to systematically functionally characterize ASDassociated genes in vivo. Using our custom machine vision system we quantified 26 phenotypes spanning morphology, locomotion, tactile sensitivity, and habituation learning in 87 strains each carrying a mutation in an ortholog of an ASD-associated ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 173 publications
(199 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have used C. elegans morphology and locomotion as readouts of disrupted behaviour in response to mutation to ASD associated genes (31,32). We have extended this analysis to inform on the effect of a neuroligin variant on a phenotype that relates to one of the triad of impairments that make up the diagnostic criteria of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have used C. elegans morphology and locomotion as readouts of disrupted behaviour in response to mutation to ASD associated genes (31,32). We have extended this analysis to inform on the effect of a neuroligin variant on a phenotype that relates to one of the triad of impairments that make up the diagnostic criteria of ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Although this learning process appears simple at first glance, previous work revealed that at least long-term habituation learning is regulated by multiple mechanisms that operate on distinct time scales 2,15 . Similarly, numerous molecular-genetic mechanisms also regulate short-term habituation learning [16][17][18][19][20][21][22][23][24][25][26] . Moreover, pharmacological screens have identified multiple neurotransmitter and neuromodulatory systems contributing to habituation 7 .…”
Section: Introductionmentioning
confidence: 99%